PENGARUH GAYA HIDUP HEDONISME DAN PERILAKU KONSUMTIF TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA SHOPEE PAYLATER - Bila, Siti Marisa; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
One of the fintech innovations that is currently popular and has become the choice of the public is shopee paylater. The existence of shopee paylater causes an increase in hedonism lifestyles and consumptive behaviors that can affect product purchase decisions. The objectives of the study are: (1) to find out the influence of hedonism lifestyle on the purchase decision of shopee paylater users (2) to find out the influence of consumptive behavior on the purchase decision of shopee paylater users (3) to find out the influence of hedonism lifestyle and synthetic behavior on the purchase decision of shopee paylater users. This type of research uses a quantitative method by distributing questionnaires through google forms to obtain the primary data needed. Furthermore, the data will be analyzed using multiple linear regression and calculated with IBM SPSS 27. The results of the study show that there is (1) a positive influence of hedonism lifestyle on the purchase decision of shopee users 2) the positive influence of consumptive behavior on the purchase decision of Shopee Paylater users (3) The positive influence of hedonistic lifestyle and consumptive behavior on the purchase decision of Shopee Paylater users. Keywords: hedonism lifestyle, consumer behavior, purchasing decisions